Pavetta trichardtensis (Rubiaceae) and its varieties - Hahn, Norbert (Phytotaxa, 2022)
This article attempts to resolve the long-standing confusion surrounding the identities of Pavetta hirtiflora and Pavetta zoutpansbergensis, both treated as synonyms of Pavetta trichardtensis. It is proposed that the P. trichardtensis complex be split into two varieties. Extensive field work and investigation of herbarium specimens supported these two varieties as distinct and occurring on the Blouberg, Soutpansberg and Wolkberg ranges. The typical pubescent variety occurs on the Soutpansberg through to the Wolkberg and the glabrous variety occurs on the Soutpansberg, Blouberg and possibly Houtbosch (Woodbush).